Development of a Controlled Medical Terminology: Knowledge Acquisition and Knowledge Representation - Musen, M. A.; Wieckert, K. E.; Miller, E. T.; Campbell, K. E.; Fagan, L. M. (Methods of Information in Medicine, 1995)
The creation of controlled medical terminologies is a central challenge in the development of electronic patient records. In the T-HELPER patient-record system, designed for the care of patients with HIV diease, the IVORY module allows health-care workers to compose textual progress notes by making selections from menus generated automatically from a controlled medical terminology. Construction of this IVORY terminology required extensive design sessions with a team of computer scientists and an expert physician. Refinement of the terminology was only possible when the design team could envision how the completed T-HELPER system would be used in the context of clinical practice. Development of controlled medical terminologies is a significant problem in knowledge acquisition. Techniques used to acquire and represent clinical concepts for the purpose of building decision-support systems also are appropriate for the construction of controlled terminologies such as the one in T-HELPER.
Keywords: Controlled Medical Terminology; Knowledge Acquisition; Participatory Design; T-HELPER System; IVORY System